Critical finger ischemia and myocardial fibrosis development after sudden interruption of sildenafil treatment in a systemic sclerosis patient - C. Bruni; S. Bellando-Randone; L. Gargani; E. Picano; A. Pingitore; M. Matucci-Cerinic; S. Guiducci (PAGEPress Publications, 2016)
Systemic sclerosis (SSc) is a connective tissue disease frequently associated with Raynaud's Phenomenon (RP). Among possible pharmacological treatments, phosphodiesterase 5 inhibitors are considered in cases of severe non -responsive RP. We present the case of a male SSc patient wh presented with critical finger ischemia and concomitant appearance of myocardial fibrosis after sudden interruption of sildenafil treatment.